The Role of Metabotropic Glutamate Receptor Genes in Schizophrenia - Maj, Carlo; Minelli, Alessandra; Giacopuzzi, Edoardo; Sacchetti, Emilio; Gennarelli, Massimo (Current Neuropharmacology, 2016)
Genomic studies revealed two main components in the genetic architecture of schizophrenia, one constituted by common variants determining a distributed polygenic effect and one represented by a large number of heterogeneous rare and highly disruptive mutations. These gene modifications often affect neural transmission and different studies proved an involvement of metabotropic glutamate receptors in schizophrenia phenotype. Through the combination of literature information with genomic data from public repositories, we analyzed the current knowledge on the involvement of genetic variations of the human metabotropic glutamate receptors in schizophrenia and related endophenotypes. Despite the analysis did not reveal a definitive connection, different suggestive associations have been identified and in particular a relevant role has emerged for GRM3 in affecting specific schizophrenia endophenotypes. This supports the hypothesis that these receptors are directly involved in schizophrenia disorder.
Keywords: antipsychotic drugs